(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study explores how artificial intelligence (AI) enhances personalization in e-commerce platforms and its influence on consumer purchasing decisions. By analyzing data from leading online retailers, the research investigates the effectiveness of recommendation engines, dynamic pricing, and personalized marketing. The findings suggest that AI-driven personalization significantly increases customer engagement and conversion rates, though it also raises ethical concerns around data privacy and algorithmic bias.